Insights about the Sines massif: a reinterpretation of geophysical data to the assessment of the potential for CO2 storage through mineral carbonation - Marques, Fábio (2022)
ABSTRACT: The InCarbon project aims to evaluate the potential for storage of captured CO2 using in-situ mineral carbonation in mafic and ultramafic plutonic rocks in Alentejo, Portugal. The Sines massif appears to be the most promising massif for mineral carbonation and its geochemistry, petrography, mineralogy, volume and extension are characterized. Its offshore volume and extension are evaluated through reinterpretation of previous geophysical data which confirms the occurrence of two well defined magnetic anomalies. The Sines magnetic anomaly is directly related with the outcropping area of the Sines massif to the continental shelf; three-dimensional modelling (3D) of apparent magnetic susceptibility correlates with a volume of 217 km3.The offshore magnetic anomaly presents an estimated volume of 226 km3 and is located about 10 km from the Sines anomaly to the Southwest. If both anomalies result from a single igneous body, the area of the Sines massif could as be large as 300 km2. However, the possibility of these that those two anomalies correspond distinct mafic igneous structures in the continental shelf cannot be discarded and should be further investigated.